Research on Electric Energy Measurement Method of Rail Transit Train - ZHOU Xiaoling; CHEN Mingyang; SHANG Jing; GAO Liansheng; WANG Yimin; DONG Zhiran (Kongzhi Yu Xinxi Jishu)
Electric energy measurement system of rail transit train has no national standard. At present, IEC 61000-4-30 Electromagnetic compatibility-Part 4-30:Testing and measurement techniques-Power quality measurement methods is only applicable to power frequency (50 Hz or 60 Hz) power quality measurement methods. With the rapid development of rail transit equipment and technology, in order to apply the current nominal traction system AC voltage frequency (50 Hz or 16.7 Hz) and DC-powered electric energy measurement, this paper puts forward measurement methods of voltage, current and electric energy and a new method of uncertainty calculation of active power, according to IEC 62888-2:2018 Electric energy measurement of rail transit trains -Part 2: Electric energy measurement. Combined with the research results of design and application of electric energy test system, typical solutions of train electric energy measurement system are provided. Practical measurement results show that by these solutions, relative uncertainty of active power of the system is better than 4‰, which meets and exceeds the requirements of international standards, and the correctness of the new calculation method of the uncertainty of active power is verified.